ANALISIS KENAIKAN TEMPERATUR OLI PELUMAS PADA BANTALAN PENYANGGA BAWAH (LOWER GUIDE BEARING) DI UNIT 4 PLTA SINGKARAK - Dedi Wardianto (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
Singkarak hydro power plant is one of the largest power generation to meet theelectricity needs of West Sumatra with a capacity of 175 MW with four units generatingmachine. Unit 4 Singkarak hydro power plant experiencing abnormalities of the lubricating oiltemperature in the lower guide bearing genarator resulting in decreased generation unitinstalled capacity of 10 MW and the changing patterns of operation and maintenance. Thisthesis aims to find the root of the problem that caused the rise lubricating oil temperature aswell as finding a solution fixes the problem. The method used to analyze using the tool RCFA(root cause failure analysis) which is an investigation process to determine the main causes ofa failure mode.From the analysis, we concluded that the formulation RCFA rise oil temparature oflower guide bearing oil due to low flow rate of lubricating oil resulting decline in maximumheat transfer is from 71 kW to 45.54 kW and due to the clearance between the bearing of theshaft does not correspond with the allowed values the manufacturer of the engine when viewedwith shaft deflection values that occurred in unit 4 Singkarak hydro power plant evidenced bythermal produced (Hg) greater value five-fold in the amount of 14.133 kW.Keywords: Lower guide bearing, Oli lubricants, Oil flow, Clearance bearings.